4(2m-3)+4m+7=67

Simple and best practice solution for 4(2m-3)+4m+7=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2m-3)+4m+7=67 equation:


Simplifying
4(2m + -3) + 4m + 7 = 67

Reorder the terms:
4(-3 + 2m) + 4m + 7 = 67
(-3 * 4 + 2m * 4) + 4m + 7 = 67
(-12 + 8m) + 4m + 7 = 67

Reorder the terms:
-12 + 7 + 8m + 4m = 67

Combine like terms: -12 + 7 = -5
-5 + 8m + 4m = 67

Combine like terms: 8m + 4m = 12m
-5 + 12m = 67

Solving
-5 + 12m = 67

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 12m = 67 + 5

Combine like terms: -5 + 5 = 0
0 + 12m = 67 + 5
12m = 67 + 5

Combine like terms: 67 + 5 = 72
12m = 72

Divide each side by '12'.
m = 6

Simplifying
m = 6

See similar equations:

| x+9=17+5x | | 12k=-12 | | -6(x+4)=-12(x+1) | | 4(3x+2)=12x-1 | | 2z=8(z-5) | | 21x-28x= | | x+25=13 | | -1y=-7x+32 | | 3-7x=3(5-3x) | | t^2+30t+392.7=0 | | 5x+3=-6x-41 | | C(e)=.20e+27.27 | | -3x-9=4x+54 | | 18-1/2x=12 | | -2w-7=-12w+6 | | t(t-30)+392.7=0 | | 9x+63+xy+7y=0 | | -49=5+5x | | 40=-4.9t^2+30t+12 | | 9x+63+cry+7y=0 | | 5x+6=x-38 | | -2+5x=4-3x | | 12v=8v+36 | | 3(10+5b)+4b=-11(1+2b) | | 10x+4=15x-7 | | 5600e^5k=6300 | | 48=38+.99n | | 40-v=7v | | 8.1E+12= | | -[y^2-2]=y^2-5-2y^2 | | 48.00=38.00+.99n | | 40=4.9t^2+30t+12 |

Equations solver categories